Di Tepi Zaman: Istana Niat Lima Laras dan Eksistensinya di Kabupaten Batubara - Dharma Kelana Putra (Jurnal Community, 2023)
This study describes the Istana Niat Lima Laras as one of the Presumed Cultural Heritage Objects (ODCB), with essential values but in endangered conditions. This study was conducted with the argument that various problems are related to efforts to preserve the Niat Lima Laras Palace. This research was conducted using a descriptive qualitative method in line with the problem. Meanwhile, the data was collected using observation techniques, interviews, documentation, and desk study. The results of the study confirm that this building does have essential values, such as educational values, historical values, cultural values, and so on. These values are crucial not only for the local community but also for this country. Then, the current condition of the building is very apprehensive. The damage suggests that this cultural heritage building is on the verge of collapse and requires attention from various parties to be preserved. Furthermore, various problems related to preservation, development, and utilization cause the government to intervene by turning these cultural heritage buildings into state assets before these historic buildings are lost to the ages.